Pendampingan Optimalisasi Peran Masyarakat Untuk Desa Progresif Dengan Asas Kemaslahatan Di Era Reformasi Industri 4.0: (Studi Lapangan di Desa Jambearum, Kec. Patebon Kab. Kendal Jawa Tengah) - Novi Cahyaningsih; Faliqul Isbah (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Optimization and the role of the community to realize a progressive village is not something that cannot be done, this study aims to provide information on the importance of the involvement of the community's role in an effort to provide benefits for the village where they live. The research method used is qualitative, namely the type of research on the condition of natural objects. Where the researcher as a key instrument, through data collection techniques the samples taken reflect representative for the population. Continuing to collect supporting data through interviews, literature studies and several other secondary efforts that support the optimization of service. The involvement of all elements of society in realizing a progressive village with a sense of benefit is absolute. The Village Government, Community Leaders, Religion and the whole community in general must be directly involved in providing assistance, suggestions, ideas, ideas that support the success of the program. The implementation of activities that can foster community enthusiasm can be one of the solutions for achieving this program. Among them are: Teaching Service to share knowledge (MERUBEL) and get to know about the village through online media (MESEDEVO). Keywords: Optimization, Society, Progressive, Benefit